2021
DOI: 10.5430/rwe.v12n1p238
|View full text |Cite
|
Sign up to set email alerts
|

Does Tax Knowledge Motivate Tax Compliance in Malaysia?

Abstract: This study aims to clarify whether tax knowledge of individual taxpayers motivates tax compliance in Malaysia. Studies with similar topics express the fact that there still exists a gap in profiling the demographic characteristics of knowledgeable taxpayers and better compliant taxpayers in Malaysia. Age, gender, income groups, and education level were the demographic variables used to study the association. The study applied a survey method for data collection. The population targeted was the individual taxpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
1
5
0
2
Order By: Relevance
“…The first hypothesis establishes a negative and insignificant effect between tax knowledge and voluntary tax compliance. The finding is in line with the previous study of (Loo et al, 2010;Salawati et al, 2021). This indicated that taxpayers do not have the technical knowledge to compute their tax liabilities or they find it difficult when doing the calculation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The first hypothesis establishes a negative and insignificant effect between tax knowledge and voluntary tax compliance. The finding is in line with the previous study of (Loo et al, 2010;Salawati et al, 2021). This indicated that taxpayers do not have the technical knowledge to compute their tax liabilities or they find it difficult when doing the calculation.…”
Section: Discussionsupporting
confidence: 91%
“…The research recommends that government to use tax education to improve tax compliance among the taxpayers. Hence, Salawati et al (2021) found a negative and insignificant between tax knowledge and tax compliance among taxpayers. The study was conducted in Malaysia to examine the influence of tax knowledge on tax compliance.…”
Section: Tax Knowledgementioning
confidence: 88%
“…Penelitian yang dilakukan oleh (Alkhatib et al, 2020;Alshirah et al, 2022;Mansur et al, 2022;Oktaviani et al, 2019), menyatakan bahwa terdapat hubungan positif dan signifikan antara variabel pengetahuan perpajakan dan kepatuhan wajib pajak. Sedangkan, penelitian yang menghasilkan temuan yang berbeda yakni hubungan yang tidak signifikan antara pengetahuan perpajakan dan kepatuhan wajib pajak ditemukan dalam penelitian yang dilakukan oleh (Hantono & Sianturi, 2021;Hendrawati et al, 2021;Newman et al, 2018;Salawati et al, 2021;Twum et al, 2020).…”
Section: Studi Literaturunclassified
“…Certain roles and duties in a business entity are assigned to the employees of the business entity to be performed on behalf of the business entity. The revenue collected by the 'Inland Revenue Board of Malaysia' (IRBM) from the corporate sectors, through direct taxation, is the main source of income contributed to the tax cluster (Sritharan et al, 2021). Although the contributed revenue becomes higher and higher, the decisions made on the tax affairs are decided by a natural person.…”
Section: Factors That Impact Upon Personal Tax Compliancementioning
confidence: 99%